2019
DOI: 10.14701/ahbps.2019.23.1.56
|View full text |Cite
|
Sign up to set email alerts
|

Effect of early and delay starting of enteral feeding in post-pancreaticoduodenectomy patients

Abstract: Backgrounds/Aims This study was undertaken to see the effect of early starting of enteral feeding after pancreatoduodenectomy (PD). The results were compared with existing nutritional practice in which enteral feeding started, usually after 7 to 8 postoperative day (PODs) in our institute. Methods Thirty patients whome underwent a PD from January 2016 to December 2016 were included in the study. They were divided into two groups, I and II. In group I (n=15), enteral fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…However, no meta-analysis has studied the effect of early EN on nutritional status. Das et al [ 9 ] showed that early EN support cannot significantly improve the nutritional status of patients compared with traditional nutritional support. This study aimed to quantitatively investigate the effect of early nutritional support on nutritional status of patients undergoing gastrointestinal surgery based on meta-analysis.…”
Section: Introductionmentioning
confidence: 99%
“…However, no meta-analysis has studied the effect of early EN on nutritional status. Das et al [ 9 ] showed that early EN support cannot significantly improve the nutritional status of patients compared with traditional nutritional support. This study aimed to quantitatively investigate the effect of early nutritional support on nutritional status of patients undergoing gastrointestinal surgery based on meta-analysis.…”
Section: Introductionmentioning
confidence: 99%